The Spectral Radiative Properties of Stratus Clouds and Ice Surfaces in the Arctic - Hobbs, Peter V (1997)
The heat budget of the Arctic is determined in large part by the amounts of solar radiation absorbed, reflected and transmitted by clouds, aerosols and underlying surfaces. The long-term goal of this project is to obtain measurements of these quantities that can be used in modeling studies of the heat budget of the Arctic.